The role of human capital, social capital, and psychological capital in micro-entrepreneurship in China - Schwarz, Susan (2017)
A key question in entrepreneurship research is how certain individuals in different contexts are able to generate superior venture performance. Micro-entrepreneurs in emerging and transition economies lack access to various forms of capital to launch and grow new ventures, as they operate in settings characterised by resource scarcity and underdeveloped market institutions. To meet the need for tangible financial resources, lenders provide small loans to stimulate business development. Yet financial capital alone does not ensure successful business outcomes, raising questions as to how micro-entrepreneurs deploy intangible resources to drive growth. Based on in-person survey interviews conducted with 164 entrepreneurs receiving loans at community banks in Zhejiang Province, China, as well as qualitative field data, this study examines the impact of human capital, social capital, and psychological capital on the growth of micro-enterprises in China, with a focus on the moderating role of psychological capital. By integrating psychological capital with human capital and social network approaches, this study fills a research gap at the intersections of these three perspectives. The contributions of this study include establishing boundary conditions for these theories to explain how entrepreneurs overcome resource scarcity to grow ventures within a relational society undergoing a transition to a market economy.